A family of fifth-order convergent methods for solving nonlinear equations using variational iteration technique. Issue 3 (3rd April 2018) - Zhang, Xiujun; Shah, Farooq Ahmed; Li, Yingfang; Yan, Li; Baig, Abdul Qudair; Farahani, Muhammad Reza
Abstract: In this paper, we suggest and analyze new higher order family of iterative methods for solving nonlinear equations by using variational iteration technique. We give several examples to illustrate the efficiency of the proposed methods. Comparison with other similar methods is also given. New methods can be considered as an alternative of the existing methods. This technique can be used to suggest a wide class of new iterative methods for solving nonlinear equations.